Battle of the platforms. (Economist, 2001)
Discusses the outlook for so-called web services, in which machines will be able to communicate via the Interent and provide various electronic offerings. Example of ADP, which distributes employee paychecks, as a pioneer in web services; Battle in the software industry over which platform, or operating system, will support web services, including Sun Microsystems' Java and the Microsoft .NET program; Background on web services, including the role of middleware.